Ask Question
2 April, 03:39

How do you solve 12 (x+3) = 4 (2x+9) + 4x

+1
Answers (2)
  1. 2 April, 04:11
    0
    Answer: x=1

    Step-by-step explanation:

    • Substitute, so 12x+36 = 8x+36+4x

    • Add 8x and 4x

    • 12x+36 = 12x+36

    Right away you can tell that they will equal each other if you plug in 1, then check your answer by plugging 1 into x
  2. 2 April, 05:37
    0
    the solution is all real numbers

    Step-by-step explanation:

    12 (x+3) = 4 (2x+9) + 4x

    distribute

    12*x + 12*3 = 4*2x + 4*9 + 4x

    simplify

    12x+36 = 8x + 36 + 4x

    combine like terms

    12x + 36 = 12x + 36

    subtract 12x from each side

    12x - 12x + 36 = 12x - 12x + 36

    36 = 36

    this is always true

    it does not matter what value I put in for x in the original equation, it will always be true

    the solution is all real numbers
Know the Answer?
Not Sure About the Answer?
Get an answer to your question ✅ “How do you solve 12 (x+3) = 4 (2x+9) + 4x ...” in 📙 Mathematics if there is no answer or all answers are wrong, use a search bar and try to find the answer among similar questions.
Search for Other Answers